Penentuan Kualitas Bibit Padi Menggunakan Metode Fuzzy Mamdani - Furqan, Mhd.; Sriani, S; Hasugian, Abdul Halim; Hsb, Munawir Siddik (STIKOM Tunas Bangsa Pematangsiantar, 2021)
the agriculture sector still faces fairly basic challenges, namely the quality problem and the increase in competitiveness through productivity and efficiency. This research determines the criteria for the best quality types of rice seeds and how to apply the Fuzzy Mamdani Method, to determine the quality of rice seeds in order to assist farmers in determining the quality of the best rice seeds. Mamdani fuzzy method is one example of a method that can help the optimal decision making process to solve practical problems. The problem solved is the determination of the best quality of rice seeds, based on established criteria, namely the type of rice, the shape of the rice, the color of the seeds, the age of the seeds, and roots. This is done to reinforce the output or output of each input variable membership. Then after the output input output variable is determined, the implementation of the rules for each parameter is carried out. After that do defuzzyfication with the centroid method. So that the output of one parameter is 60 with verry good information. This system was built with a website application where the application is able to help users to determine the quality of rice seeds and obtain information about the best seeds.